Об исключении сжатия цилиндрической оболочки после "среза" импульса внешнего магнитного поля - Живанков, К.И.; Михайлов, В.М. (Електротехніка і електромеханіка, 2011)
Furth’s idea of inductor shorting to prevent current oscillations after pulse shaving for avoidance of internal cylindrical conducting shell compression after the shell magnetic-impulse extension by negative pressure forces is theoretically verified. Feasibility of the shaving impulse frequency and magnitude increase along with negative pressure gain is also shown as compared with a scheme without inductor shorting.